THE EFFECT OF FRANGIPANI FLOWER ETHANOL EXTRACT ON SUPEROXIDE DISMUTASE (SOD) LEVELS IN MALE RATS EXPOSED TO CIGARETTE SMOKE AND VAPE - Austin Widyasari Wijaya Putu; Pharmawati Made; Evayanti Luh Gde; Sri Ekayanti Ni Wayan; Indah Kusumadewi Riandra Ni Putu; Hwee Ming Cheng (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2025)
Abstract Background: Both types of cigarettes (traditional and electronic) have negative health effects, and public interest remains high. Based on several studies, antioxidants are known to counteract the effects of ROS caused by cigarettes. One of them is frangipani (Plumeria alba), which has phenols and flavonoids.Objective: To find out the antioxidant effects of frangipani flower extract on test animals exposed to cigarette and vape smoke.Methods: An experimental method with a randomized post-test control group design was used in this study. The sample consists of healthy male Wistar rats divided into five sample groups, which received intervention for a 3-week duration. Data were analyzed using one-way ANOVA followed by post hoc tests.Results: This study found that both cigarettes and vaping lowered SOD levels (P1 and P2 groups; 3.381 and 4.462 ng/mL). Meanwhile, the groups with frangipani flower extract, who were exposed to cigarettes and vaping, had a higher level of SOD (P3 and P4; 6.999 and 8.681 ng/mL).Conclusions: The administration of frangipani flower extract containing antioxidants has a positive effect on SOD levels.